Biochemical Composition of Yellow Stripe Scad, Selaroides leptolepis as a Function of Maturity Stage and Length - S., David Kingston; V.K., Venkataramani (Fishery Technology, 2025)
The biochemical composition of Selaroides leptolepis was studied in different maturity stages as well as in different length groups. The juveniles contained more protein (76.92%) than males (73.92%) and females (69.24%). With the advancement of maturity, a decrease in moisture as well as protein was noticed whereas a positive relationship was noticed with fats. Spent animals showed distinct variations. Protein and fat followed an inverse relationship.